Maintenance management of public building managed by Majlis Bandaraya Kuala Terengganu (MBKT) / Nor Zuraida Razali - Razali, Nor Zuraida (Faculty of Architecture, Planning and Surveying, 2009)
Generally knew that maintenance management is one of the important aspects that could not handle in uncared and it should apply in each building. This is to ensure the building is managed in well function and efficiently. Maintenance management includes the organisation structure, maintenance policy, maintenance budget, the needs of maintenance management, and others related that can be various kind of it. This dissertation is covering the definition of maintenance management at public building, the effectiveness of maintenance management managed by chosen case study and the performance of the building. The selected case study use for the research is Majlis Bandaraya Kuala Terengganu (MBKT) and another three public building manage under this council. In addition, the information was gathered by interview, questionnaire, internets, books and others related on it. From this study, the author hopes that it will give the clear information to the readers and can be as reference in the future.